The Relationship Between Loneliness, Life Satisfaction and Internet Addiction Among Young Adults - Wong, Xi Yu (2016)
A cross sectional was occupied in this study to examine the relationship between loneliness, life satisfaction and internet addiction among young adults. A total of 300 undergraduates from UTAR Perak campus were participated through convenience sampling. A selfadministered questionnaire which consisted Internet Addiction Test, Satisfaction with Life Scale, and UCLA Loneliness Scale Version was employed. Travis Hirschi’s Social Bond / Social Control Theory was adapted in this study to explain the relationship of loneliness and life satisfaction, and internet addiction. Pearson Correlation was employed and revealed significantly positive relationship between internet addiction and loneliness (r = 0.675); meanwhile the relationship between internet addiction and life satisfaction were also found to be significant but negatively associated (r = -0.501). Furthermore, multiple linear regression was run to figure out the predictor of internet addiction between loneliness and life satisfaction and findings showed two predictors statistically significantly predicted internet addiction, F(2, 297) = 150.999, R² = .504. Specifically, loneliness best predicted internet addiction. Lastly, male (M = 49.56, SD = 12.49) and female (M = 46.28, SD = 12.78) differ significantly in internet addiction, t(298) = 2.232. All the results were analyzed with SPSS 23.0 software.